1985
DOI: 10.3758/bf03207649
|View full text |Cite
|
Sign up to set email alerts
|

Microcomputers in social psychophysiological research: An overview

Abstract: Microcomputer systems have become commonplace in the psychophysiological laboratory during the past 5 years and are currently used in all phases of data acquisition, experimental control, and data analysis. In the past year, however, advances in microprocessor technology and scientific software have greatly extended the capabilities ofthese desk-top systems. Small laboratories now can afford an integrated laboratory microcomputer system and both the high-fidelity data acquisition hardware and the sophisticated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Our analyses revealed that the 2 kHz and 10 kHz sampling rates resulted in statistically different NCV values, but the difference was very small (less than 0.2 ms, which is practically negligible). Since the sampling rate is controlled by the microprocessor in the data logger and this component is directly related to the cost of the equipment [16], using a 2 kHz sampling frequency is advantageous in terms of simplicity, potentially decreasing the cost of production of the NCV equipment. Furthermore, using a lower sampling frequency of 2 kHz can minimize the required computer storage capacity for saving EMG data.…”
Section: Discussionmentioning
confidence: 99%
“…Our analyses revealed that the 2 kHz and 10 kHz sampling rates resulted in statistically different NCV values, but the difference was very small (less than 0.2 ms, which is practically negligible). Since the sampling rate is controlled by the microprocessor in the data logger and this component is directly related to the cost of the equipment [16], using a 2 kHz sampling frequency is advantageous in terms of simplicity, potentially decreasing the cost of production of the NCV equipment. Furthermore, using a lower sampling frequency of 2 kHz can minimize the required computer storage capacity for saving EMG data.…”
Section: Discussionmentioning
confidence: 99%
“…However, with the rapid development of wireless networks, miniaturized sensors, body area networks, and reconfigurable biosignal recording devices (e.g., [3,122,135,381,460,610,713]), this traditional disadvantage is quickly vanishing [98,121,321,403,508,571,658,702] (cf. [642]). Physiological signal recording apparatus has already been integrated in tools such as helmets, beds, music players, gaming consoles, or clothes [10,101].…”
Section: Biosignalsmentioning
confidence: 99%
“…These include such languages as Maple, MATLAB, and ASYST (Tassinary, Marshall-Goodell, & Cacioppo, 1985). Our choice of Mathematica 3 years ago was based on features now shared by many of these packages.…”
Section: A Hybrid Approach To Erp Analysismentioning
confidence: 99%